Implementasi Restoratif / Restorative Justice Dalam Penyelesaian Tindak Pidana Kecelakaan Lalu Lintas Yang Dilakukan Oleh Anak Di Polres Rembang - Annis Nurwianti; Gunarto Gunarto; Sri Endah Wahyuningsih (Jurnal Hukum Khaira Ummah, 2017)
The traffic accidents enhancement that occurred recently by the children as perpetrators who caused death victims incised black sheets in the traffic law. What people see about an accident occurred was completely the driver error. Meanwhile, according to legal theory that the accident must be seen from the major factor which caused the traffic accidents. This research investigate the implementation, constraints and its solutions in the implementation of restorative justice as a settlement form of traffic accident by children in Polres Rembang. Therefore this study intends to analyze the implementation of restorative justice, analyze the constraints faced by the Investigator and determine the solution of the constraints in the implementation of restorative justice to traffic accidents involving the child as a suspect traffic accident in the Rembang District police territory.The Rembang city police solves the incidents of traffic accidents with children as perpetrators through a diversion process, this was aimed to avoid the children from detention, and from being labeled as a criminal, and teachs the children to responsible for what tey have been done. The problem occurred in implementating the restorative justice were the perpetrators are less cooperative with the victim after the accident, the victim did not want to forgive the perpetrators and the existence of third person who gave bad doctrin, and also the lack of information abaut divesion process in society. The Rembang City Traffic Unit police Officers attempts to avoid conflict / complaints from the victims are, the the officers h neutral, the perpetrators are directed to conduct a good relationship and convey condolences to the victims, conduct deliberation and ask for assistance from the Correctional Institution. Keywords: restorative justice, traffic accident, child offender